2010
DOI: 10.1007/s00464-010-1245-1
|View full text |Cite
|
Sign up to set email alerts
|

Determining scope position during colonoscopy without use of ionizing radiation or magnetic imaging: the enhanced mapping ability of the NeoGuide Endoscopy System

Abstract: Three-dimensional map images generated by the NeoGuide endoscopy system provide accurate information regarding tip position, insertion tube position, and colonic looping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…While these tendon-driven mechanisms are commonly applied as manually-operated instruments, noteworthy efforts have been made to robotize them for catheters [612] and endoscopes [1316] with higher DOF motion. In particular for tendon-driven endoscopes, tendon-driven mechanism is used to aim cameras to intended surgical sites while avoiding complexity of control for multiple bending sections and multiple tendons.…”
Section: Introductionmentioning
confidence: 99%
“…While these tendon-driven mechanisms are commonly applied as manually-operated instruments, noteworthy efforts have been made to robotize them for catheters [612] and endoscopes [1316] with higher DOF motion. In particular for tendon-driven endoscopes, tendon-driven mechanism is used to aim cameras to intended surgical sites while avoiding complexity of control for multiple bending sections and multiple tendons.…”
Section: Introductionmentioning
confidence: 99%
“…MEI is currently used to aid performance assessment during the Bowel Cancer Screening accreditation process in the United Kingdom, and some evidence from single-center studies has demonstrated that it can enhance the acquisition of colonoscopy skills in trainees [17,18]. A novel computer-assisted colonoscope (NeoGuide Endoscopy System) that generates real-time three-dimensional map images of the scope and the colonic lumen is effective in providing accurate information regarding tip position, insertion tube position, and colonic looping [19].…”
Section: General Principles and Simple Maneuversmentioning
confidence: 98%
“…The platform allows the colonoscopist to have accurate images of the tip position, endoscope shaft configuration and luminal views. 19 …”
Section: Neoguide (Intuitive Surgical)mentioning
confidence: 99%